Uso de redes sociales y habilidades sociales en los alumnos del 5º año de una Institución Educativa Particular Religiosa de Lima Metropolitana, 2011 - Mejía Bejarano, Gabriela (2019)
Objective: To determine the relationship between the use of social networks and social skills in students of the 5thyear of a religious private school in Lima. Materials and methods: Design nonexperimental, cross-sectional anddescriptive-correlational followed 59 male and female students of a private educational institution in Punjab religious who were in the 5th year of high school, who have applied questionnaire using self-created Social Network(2011) and the Social Skills Scale (EHS) Gismero (2000). Results: The results show a low but significant correlationbetween use of social networking and social skills. Also at all dimensions of social skills scale, it has become clearthat the category of self-expression in social situations has been the most affected in relation to the use of socialnetworks. Conclusions: After the analysis is concluded that there is a low inverse correlation between the use ofsocial networks and social skills, therefore a greater use of social networking behavior less skillful.